ON SOME OF THE REASONS IN THE REGULATORY LEGAL ACTS THAT INFLUENCE THE OCCURRENCE OF CORRUPTION - Aloev Ulugbek Mahmudovich; Rozimova Kunduz Yuldashevna; Heybatollah Najandiamnesh (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes some of the factors in national legislation acts that can lead to corruption. In particular, in terms of factors leading to corruption, the authors analyzed the high cost of compliance with the requirements of regulatory legal acts for citizens, the granting of unnecessarily broad powers to state bodies, as well as anti-corruption expertise of regulatory legal acts. The article developed proposals and recommendations for eliminating factors leading to corruption.